Faber Polynomial Coefficient Estimates for Meromorphic Bi-Starlike Functions. (13th March 2013) - Hamidi, Samaneh G.; Abd Halim, Suzeini; Jahangiri, Jay M.
Abstract : We consider meromorphic starlike univalent functions that are also bi-starlike and find Faber polynomial coefficient estimates for these types of functions. A function is said to be bi-starlike if both the function and its inverse are starlike univalent.